Demystifying Intrapreneurship: The Mediating Role of Middle Management in Nurturing Innovation Across Large Organizations - Pandey, Sharadkumar B (Digital Repository of Theses, 2024)
In the tumultuous landscape of modern corporate dynamics, innovation and organizational rejuvenation emerge as non-negotiable imperatives. This study ventures into the strategic realm of middle managers, illuminating their pivotal role in fostering intrapreneurship to cultivate an environment teeming with innovation within organizations. Through a rigorous examination of the intricate interplay between demographics, organizational variables, and key factors of innovation, including technological adaptation and the strategic influence wielded by middle-level managers, this research endeavors to unveil the fundamental elements underpinning a thriving culture of innovation. Harnessing a quantitative methodology firmly anchored in the post-positivist paradigm, this study meticulously dissects the strategies deployed by middle managers to cultivate intrapreneurial talent and ignite the flames of innovation. By unraveling the complex tapestry of individual and organizational dynamics, it offers a holistic understanding of the mechanisms driving innovation within corporate ecosystem. Ultimately, this paper transcends mere scholarly discourse, offering actionable insights tailored to empower managers amidst the storm of unprecedented disruption. It underscores the indispensable role of middle managers as vanguards of innovation in the relentless march towards organizational excellence in today's dynamic corporate landscape.